2015
DOI: 10.1088/2041-8205/811/2/l26
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Rigidly Rotating Magnetosphere Stars Hd 345439 and Hd 23478

Abstract: The SDSS III APOGEE survey recently identified two new σ Ori E type candidates, HD 345439 and HD 23478, which are a rare subset of rapidly rotating massive stars whose large (kGauss) magnetic fields confine circumstellar material around these systems. Our analysis of multi-epoch photometric observations of HD 345439 from the Kilodegree Extremely Little Telescope, Wide Angle Search for Planets, and ASAS surveys reveals the presence of a ∼0.7701 day period in each data set, suggesting the system is among the fas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
4
22
1
Order By: Relevance
“…The stellar rotation period of ρ Oph A derived in Sec. 3 (≈ 0.75 days) is very close to the rotation period of another B2type star: HD 345439, P rot ≈ 0.77 days (Wisniewski et al 2015;Hubrig et al 2017). At the present time, ρ Oph A is the third-most rapidly rotating magnetic B-type star yet discovered, after HR 5907 (Grunhut et al 2012) andHR 7355 (Rivinius et al 2013), both stars having rotation periods of ≈ 0.5 days.…”
Section: The Orm Geometry Of ρ Oph Asupporting
confidence: 64%
“…The stellar rotation period of ρ Oph A derived in Sec. 3 (≈ 0.75 days) is very close to the rotation period of another B2type star: HD 345439, P rot ≈ 0.77 days (Wisniewski et al 2015;Hubrig et al 2017). At the present time, ρ Oph A is the third-most rapidly rotating magnetic B-type star yet discovered, after HR 5907 (Grunhut et al 2012) andHR 7355 (Rivinius et al 2013), both stars having rotation periods of ≈ 0.5 days.…”
Section: The Orm Geometry Of ρ Oph Asupporting
confidence: 64%
“…With time baselines of up to 10 yr, a typical cadence of 30 minutes, and the precision to detect periodic signals down to approximately one to a few millimagnitudes, KELT light curves are well-suited to the detection of the periodic variability exhibited by β Cephei stars. The utility of KELT light curves to detect periodic oscillations in brightness was demonstrated by Cargile et al (2014), Wisniewski et al (2015), and Labadie-Bartz et al (2017).…”
Section: Datamentioning
confidence: 99%
“…Landstreet & Borra 1978). Using Kilodegree Extremely Little Telescope (KELT) photometry, Wisniewski et al (2015) detected a rotation period of 0.7701 ± 0.0003 d with the zero point of the ephemeris JD = 2454252.3432 corresponding to the first minimum in the light curve (see their Fig. 1.).…”
Section: Period Determination From the Magnetic Datamentioning
confidence: 99%
“…Such stars are extremely rare: the discovery of HD 23478 and HD 345439 has enhanced the number of "extreme" rotators by 50% (Eikenberry et al 2014). The authors reported that the optical spectra of HD 345439 reveal strong He i lines and very fast rotation of ∼ 270 ± 20 km s −1 Subsequently, Wisniewski et al (2015) analysed multi-epoch photometric observations of this star from the Kilodegree Extremely Little Telescope, Wide Angle Search for Planets, and ASAS surveys revealing the presence of a ∼0.7701 day rotation period in each data set. The authors suggest that the He-strong star HD 345439 of spectral type B2 V is among the faster known He-strong σ Ori E analogs, ⋆ E-mail: shubrig@aip.de HR 7355 (P rot = 0.52 d - Rivinius et al 2013) and HR 5907 (P rot = 0.51 d - Grunhut et al 2012).…”
Section: Introductionmentioning
confidence: 99%